2014
DOI: 10.2136/sssaj2013.08.0351nafsc
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Fire Comparisons of Forest Floor and Soil Carbon, Nitrogen, and Mercury Pools with Fire Severity Indices

Abstract: Forest fires are important contributors of C, N, and Hg to the atmosphere. In the fall of 2011, a large wildfire occurred in northern Minnesota and we were able to quickly access the area to sample the forest floor and mineral soil for C, N, and Hg pools. When compared with unburned reference soils, the mean loss of C resulting from fire in the forest floor and the upper 20 cm of mineral soil was 19.3 Mg ha−1, for N the mean loss was 0.17 Mg ha−1, and for Hg the mean loss was 9.3 g ha−1. To assess the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…We found that fire caused forest floor thickness, C concentration, and C stocks to decline, whereas there was no effect of fire on mineral soil C or N concentrations or stocks, across coniferous and deciduous forest cover types. These results agree with estimates from an earlier, broader evaluation at this study site that included a greater range of forest cover types [Kolka et al, 2014]. However, we observed a decrease in C:N ratios in forest floor and mineral soil layers in all severity levels even when there were no significant differences in C or N stocks.…”
Section: Fire Effects On Forest Floor and Mineral Soil C And Nsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that fire caused forest floor thickness, C concentration, and C stocks to decline, whereas there was no effect of fire on mineral soil C or N concentrations or stocks, across coniferous and deciduous forest cover types. These results agree with estimates from an earlier, broader evaluation at this study site that included a greater range of forest cover types [Kolka et al, 2014]. However, we observed a decrease in C:N ratios in forest floor and mineral soil layers in all severity levels even when there were no significant differences in C or N stocks.…”
Section: Fire Effects On Forest Floor and Mineral Soil C And Nsupporting
confidence: 90%
“…Upland soils are entisols classified as well‐drained, shallow (20–50 cm) gravelly coarse sandy loam over bedrock (Quetico (Lithic Udorthents) and Insula (Lithic Dystrudepts) series) or moderately deep (50–100 cm) gravelly sandy loam over bedrock (Conic (Typic Dystrudepts) and Wahlsten (Oxyaquic Dystrudepts) series) (J. Barott, Soil Scientist, USFS Superior National Forest, personal communication). A more detailed description of the study site and the Pagami Creek wildfire has been presented previously [ Kolka et al ., ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mapping approach can further compliment more detailed field studies of vegetation dynamics by providing vegetative responses across the full range of environmental conditions, characteristic of large landscapes . Future research should address vegetation patch characteristics and scale, as well as species-specific associations and communities in terms of competition with forest regeneration (Frey et al, 2003), and how such associations might correspond with certain pre-fire cover types and structure as well as post-fire soil characteristics and fire severities (Kolka et al, 2014).…”
Section: Implications and Directions For Future Studymentioning
confidence: 99%